The affordances and constraints of information in crime prevention communities through social media - Ahmad Khan, Ali Fauzi; Bahri, Shamshul (Malaysian Journal of Library and Information Science, 2024)
Social media can provide important and useful information to communities in their fight to prevent crime. However, this capability has its downside. For every affordance social media provides, the platform presents an equally important constraint, which researchers and the public often ignore. Using an in-depth case study of social media crime prevention communities in Malaysia, this paper intends to provide a rich understanding of the information provided by social media in crime prevention. The study adopts the technology affordances and constraints theory to make sense of and explain how the information provided by social media affords and constrains the communities’ efforts to fight crime.